Percutaneous Intraspinal Navigation: Feasibility Study of a New and Minimally Invasive Approach to the Spinal Cord and Brain in Cadavers - Purdy, Phillip D. (AJNR Am J Neuroradiol, 2003)
Summary: We describe a percutaneous approach for cerebral surgical access. After lumbar puncture, the spinal subarachnoid space was traversed by using standard angiographic guidewire techniques until the introducer catheters were in the intracranial space. Under fluoroscopic guidance, the intracranial subarachnoid space was navigated, and the ventricular system entered. Subarachnoid placement was confirmed with contrast-enhanced digital angiography. Placement anterior to the brain stem was confirmed in both cadavers during dissection, and spinal navigation without cord damage from the anterior or posterior approach was confirmed in one. Percutaneous intraspinal navigation is a new route of access for cerebrospinal surgery that has many potential applications.